Cost misperceptions and energy consumption: Experimental evidence for present bias and biased price beliefs - Madeline Werthschulte; Andreas Löschel (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2019)
The aim of this study is to link variation in energy cost misperceptions to variation in households' energy consumption. The focus is on two sorts of misperceptions: First, present biased discounting of future energy costs and second, biased energy price beliefs. By running an artefactual field experiment with a representative sample of 711 participants, we gather incentivized measures of these two misper- ceptions and observe participant's revealed electricity consumption. Our main finding is that participants with present bias are predicted to consume on average 9% more electricity than participants with time-consistent discounting. Our results further suggest that neither the true marginal electricity price nor the expected marginal electricity price can predict electricity consumption. Taken together our results raise doubt in the effectiveness of classical price based policies in reducing households' energy consumption.
Keywords: C93; D15; D81; D91; Q49; 330; energy consumption; present bias; price beliefs; field experiment